2018
DOI: 10.3390/nu10070895
|View full text |Cite
|
Sign up to set email alerts
|

SunGold Kiwifruit Supplementation of Individuals with Prediabetes Alters Gut Microbiota and Improves Vitamin C Status, Anthropometric and Clinical Markers

Abstract: Kiwifruit are a nutrient dense food and an excellent source of vitamin C. Supplementation of the diet with kiwifruit enhances plasma vitamin C status and epidemiological studies have shown an association between vitamin C status and reduced insulin resistance and improved blood glucose control. In vitro experiments suggest that eating kiwifruit might induce changes to microbiota composition and function; however, human studies to confirm these findings are lacking. The aim of this study was to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 42 publications
3
23
0
Order By: Relevance
“…Thirty of 52 studies (57.7%) that investigated changes in weight and/or BMI, reported significant improvement postintervention [ 17 , 22 , 24 , 26 , 27 , 29 , 31 , 32 , 33 , 40 , 43 , 58 , 59 , 61 , 65 , 71 , 74 , 77 , 84 , 87 , 88 , 90 , 93 , 98 , 99 , 101 , 102 , 109 , 110 , 111 ]. Similar proportions of statistically significant findings were observed for the waist and hip circumferences and/or waist-to-hip ratio (17/32 studies, 53.1%) [ 17 , 18 , 24 , 26 , 32 , 33 , 38 , 58 , 61 , 62 , 84 , 87 , 88 , 101 , 102 , 108 , 109 ] as well as systolic and diastolic blood pressure (16/31 studies, 51.6%) [ 17 , ...…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Thirty of 52 studies (57.7%) that investigated changes in weight and/or BMI, reported significant improvement postintervention [ 17 , 22 , 24 , 26 , 27 , 29 , 31 , 32 , 33 , 40 , 43 , 58 , 59 , 61 , 65 , 71 , 74 , 77 , 84 , 87 , 88 , 90 , 93 , 98 , 99 , 101 , 102 , 109 , 110 , 111 ]. Similar proportions of statistically significant findings were observed for the waist and hip circumferences and/or waist-to-hip ratio (17/32 studies, 53.1%) [ 17 , 18 , 24 , 26 , 32 , 33 , 38 , 58 , 61 , 62 , 84 , 87 , 88 , 101 , 102 , 108 , 109 ] as well as systolic and diastolic blood pressure (16/31 studies, 51.6%) [ 17 , ...…”
Section: Resultssupporting
confidence: 72%
“…The effect of plant-based foods, notably fruit and vegetables were reported by nine studies [ 17 , 18 , 25 , 33 , 82 , 95 , 96 , 100 , 108 ]. Berries, which include strawberries, blueberries and cranberries, were the most studied among plant-based interventions [ 95 , 96 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SCFA producing bacteria Bi dobacteriales and Coriobacteriaceae), and their abundance was under-represented in GDM cases in our study. We also found reduced abundance of Actinobacteria members in GDM women at genus level: Rothia, Actinomyces, Bi dobacterium, and Adlercreutzia, most of which were well known SCFA producing and anti-in ammatory microbial groups [15][16][17][18], and were previously found to be reduced in patients with type 2 diabetes mellitus [19,20] or GDM women in the second trimester [5]. Similarly, another study also reported an overall decrease of Actinobacteria in GDM cases compared with controls during early pregnancy, although with a very small sample size (n = 15) [21].…”
Section: Discussionmentioning
confidence: 56%